Mengurai Kontroversi Dan Manfaat Nikah Misyar - Fatimawali; Changiz Mohiyeddini (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This paper describes the controversy surrounding the practice of nikah misyar and explores the potential benefits for couples who choose it. Through a literature analysis, this paper presents various arguments supporting and opposing nikah misyar. In doing so, the article aims to provide deeper insights into the phenomenon of nikah misyar and its contribution to the context of family life in the modern Muslim world. The research focuses on the exploration of fiqh laws by detailing these laws and the process of legal derivation (istidlal). The study involves an in-depth analysis of each opinion and the evidence supporting them. This qualitative approach collects relevant books related to the discussed theme, then presents data from the ideas and thoughts of involved scholars, and analyzes them to produce new legal conclusions. Findings from the research indicate that nikah misyar is viewed as conflicting with the high moral and social values upheld in Islamic society. Some scholars and segments of the community believe that this practice can undermine the institution of marriage and negatively impact family stability. Critics argue that this practice often sacrifices women's rights, such as the right to financial support and a stable household. However, for couples who choose nikah misyar, one of the main benefits is flexibility. Both partners can adjust their marital relationship according to their needs and life situations without being bound by traditional marriage norms. Keyword: Family; Misyar; Marriage.